Influence of luteolin on the apoptosis of esophageal cancer Eca109 cells and its mechanism of action - Shaokang Wang; Lingmeng Fu; Yi Wu; Hongmei Xiao; Jing Wang; Guiju Sun (Food Science and Human Wellness)
The present study was conducted to verify the influence of luteolin on apoptosis of Eca109 cells and to further investigate the possible mechanisms underlying its effect on apoptosis. The cells were exposed to different concentrations of luteolin (0, 40, 80, 120, 160, 200, 240 μM) for 24, 48, and 72 h respectively. The influence of luteolin on proliferation of Eca109 cells was detected using MTT assay. Eca109 cells were then treated with luteolin (0, 40, 160, 240 μM) for 24 h. The effect of luteolin on cell cycle progression and apoptosis was assayed by using flow cytometry (FCM). Expression of caspase9 and caspase3 mRNA and protein was analyzed by real-time PCR and Western blot respectively. The results showed that luteolin could inhibit the proliferation of Eca109 cells at all concentrations in a time-dependent manner and the relative inhibition rate showed an inverted U-shaped association with the concentration of luteolin. Further, the cell cycle was arrested in the S phase following treatment with luteolin. Apoptosis analysis indicated that luteolin could induce the apoptosis of Eca109 cells across the three concentration groups, which exhibited a trend of first promotional and then inhibitory with the increases in luteolin concentration. The effect of luteolin on the mRNA and protein expression of caspase 9 and caspase3 first manifested as promotion, then inhibition. Therefore, luteolin may serve a role in promoting cell apoptosis by inducing Eca109 cell apoptosis that involves the expression of caspase3, caspase9 mRNA and protein. This study provides theoretical basis for further study and clinical application of luteolin. The specific mechanism has not yet been clarified and the other activation pathways inducing apoptosis need to be further studied. Keywords: Esophageal cancer, Luteolin, Apoptosis